Block length determines the adsorption dynamics mode of triblock copolymers to a hydrophobic surface. (13th March 2016) - Xu, Yisheng; Shi, Kaihang; Zhao, Shuangliang; Guo, Xuhong; Wang, Jie
Abstract: Many material processes including surface modification and material fabrication depend on the mechanism by which polymers are adsorbed onto solid/liquid interfaces. Although the morphologies of block copolymers near the interface have been extensively investigated, the understanding of the adsorption dynamics is still limited. Here, we show that the block length determines the dynamic adsorption mode under conditions beyond the critical micelle concentration (CMC). The adsorption kinetics are investigated using in situ experimental characterization combined with Dissipative Particle Dynamics simulations. Two types of symmetrical triblock copolymers, i.e., PEO–PPO–PEO, with different hydrophilic PEO block lengths are studied. While both types of copolymers present similar adsorption dynamics at concentrations below the CMC, their dynamic adsorption modes are distinct at concentrations above the CMC. The present experimental–numerical study provides a mechanistic interpretation of this difference, which casts helpful insight for the dynamic control process of surface modification and material fabrication. Highlights: Polymer block length determines the adsorption dynamics to liquid/solid interface. Above CMC P100 polymers present three-stage adsorption and form two-layer structure. P500 polymers display monotonous adsorption and form uniform adsorbed structure. The adsorption mechanism is explored with DPD simulation from molecular interaction.